Improved rejection prophylaxis with an initially intensified dosing regimen of enteric-coated mycophenolate sodium in de novo renal transplant recipients - Budde, Klemens; Tedesco-Silva, Helio; Arns, Wolfgang; Shoker, Ahmed; Zeier, Martin; Klinger, Marian; Rosales, Beatriz; Walker, Rowan; Prestele, Hans; Vaidya, Soniya; Kuypers, Dirk (Transplantation, 2011)
Background. - Approximately half of cyclosporine A-treated renal transplant recipients do not reach sufficient mycophenolic acid (MPA) exposure in the first weeks posttransplantation with standard MPA dosing regimens. - Methods. - Here, we present a prospectively planned meta-analysis of data from two 6-month parallel-run studies that evaluated the effect of an initially intensified versus standard dosing regimen of enteric-coated mycophenolate sodium (EC-MPS). Four hundred forty-one de novo renal transplant recipients were randomized (1:1) to intensified (2 weeks 2880 mg/d; subsequently 4 weeks 2160 mg/d; followed by 1440 mg/d) or standard (1440 mg/d) EC-MPS, with concomitant cyclosporine A treatment and steroids with or without anti-IL-2R induction. Primary endpoint was treatment failure (biopsy-proven acute rejection [BPAR], graft loss, or death) at month 6 posttransplantation. - Results. - Treatment failure rates were 17.4% in intensified and 22.4% in standard groups (P=0.110). The incidence of BPAR was 13.8% (intensified) vs. 19.3% (standard; P=0.034). A total of 80.5% (intensified) versus 39.0% (standard) of patients achieved 12 hr MPA-area under the curve more than 30 μg·hr/mL as early as day 3 posttransplant. Renal function, gastrointestinal symptom rating scores, and safety profiles were comparable between treatment groups. - Conclusion. - The initially intensified EC-MPS dosing regimen was associated with higher MPA exposure, significantly lower rate of BPAR, and comparable safety. However, the intensified regimen did not affect graft function or survival.
Gesehen am 24.06.2022